Lima Kualitas Sikap Komunikasi Antar Pribadi oleh Unit Customer Complaint Handling PT BNI Life Insurance - Nanda Paramithasari; Risma Kartika (CoverAge: Journal of Strategic Communication, 2017)
Each service provider company is now competing to provide the best service to every customer. As one example that is in PT BNI Life Insurance. PT BNI Life Insurance is one of the subsidiaries of Bank BNI engaged in Life Insurance. In order to provide the best service each employee is required to be able to do interpersonal communication well to customers. This is of particular concern in the customer complaint handling Unit, where the unit faces daily complaints from customers. Customers faced by customer complaint handling units have different characters. Given the different character of customer skill in interpersonal communication, customer complaint handling unit is highly considered and must be run effectively and in harmony with what is understood by the customer. The methodology used is qualitative with postpositivist paradigm. The concept used in this research is the concept of interpersonal communication, customer relationship management, service, and customers. The findings of this research, interpersonal communication conducted by customer complaint handling unit at PT BNI Life Insurance is effective because it has implemented five quality attitudes considered, namely openness, empathy, supportive attitude, positive attitude, and equality.